NaHS inhibits NF-κB signal against inflammation and oxidative stress in post-infectious irritable bowel syndrome. Issue 69 (6th July 2016) - Yang, Shenglan; Deng, Danfang; Luo, Yingying; Wu, Yanran; Zhu, Rui; Xue, Kaming; Zhou, Yanping
Abstract : In this study, the alleviating role of hydrogen sulfide (H2 S) was investigated in a Post-Infectious Irritable Bowel Syndrome (PI-IBS) murine model and Caco-2 cells. Abstract : In this study, the alleviating role of hydrogen sulfide (H2 S) was investigated in a Post-Infectious Irritable Bowel Syndrome (PI-IBS) murine model and Caco-2 cells. Murine PI-IBS model was established using Trichinella spiralis infection and the results showed that mice infected with Trichinella spiralis exhibited marked intestinal inflammatory response and oxidative injury. NaHS, a H2 S donor, injection markedly alleviated inflammatory response and oxidative injury and in vitro data further confirmed the anti-inflammatory and antioxidant functions in TNF-α treated Caco-2 cells. Meanwhile, TNF-α exposure reduced cellular H2 S level and cystathionine β-synthase (CBS), a H2 S synthesis enzyme, further exacerbated TNF-α-induced inflammation in Caco-2 cells. NaHS reversed the effect of TNF-α and CBS siRNA on cellular H2 S generation and inflammation. Furthermore, NaHS inhibited Trichinella spiralis induced NF-κB upregulation in Trichinella spiralis infected group. In conclusion, H2 S plays a beneficial role in PI-IBS model and TNF-α induced inflammation in vitro, which may involve in NF-κB signaling pathway.